Moradores crônicos de hospital psiquiátrico: um desafio à desinstitucionalização - Bezerra, Cíntia Guedes (2010)
The existence of chronic inhabitants in the psychiatric hospitals imposes a challenge to the Psychiatric Reform, that proposes things such as the gradual and progressive way to extinct mental institutions, once the permanence of the hospital in the system is only necessary because there is not a net of well structured substitute services capable of receiving that demand. This work considered relevant to deepen the knowledge about those people who passes their lives jailed by the walls of psychiatric hospitals and compose significant part of the world population. It also aimed to investigate the problem relative to the condition of being an inhabitant of a psychiatric hospital the Dr. João Machado Hospital (HJM), in the city of Natal/RN. The paper used different points of view (patients , families and professionals ) to define the profile of the inhabitants, to identify the possibility of insertion in substituting social equipment, to know the expectations of the inhabitants and their relatives regarding to the exit of the life shelter, to investigate the demands related to the net of cares social support for making feasible the discharge and to identify the difficulties that are involved in the exit of the chronic inhabitant of the hospital. There were defined three methodological phases: delineation of the identification, socio-economic and clinical profile of the inhabitants of the HJM; semi-structured interviews with professionals; and open interviews with inhabitants and family. It concluded that the psychiatric institutionalization contributes to the generation of chronic inhabitants in the psychiatric hospitals. Among the professionals, it was detached the defense of desospitalization, but an existence of devices of the asylum model. The relatives showed a resistance to participate in the care and the inhabitants exposed their desire to leave the hospital, as well like the wish of permanence. It was considered important: the construction of an extra-hospital net that enables to desinstitutionalization; the qualification of the technical; orientation to the family, stimulating its participation in the process of caring; give freedom to the individuals in mental suffering, enabling them to be ahead of their lives and express their desires and opinions; the implementation of an extended clinic that is capable of building new possibilities; and a subjectivity guided by the social enclosure